Out of the shadows : the role of social workers in disasters - Bartoli, Angie; Stratulis, Maris; Pierre, Rebekah (Critical Publishing, 2022)
This book shines a light on the personal stories of people with lived experiences and the important and valuable role that social workers have played in disaster response.